Usuário ou traficante? Critérios utilizados por operadores do direito no julgamento de adolescentes flagrados com drogas ilícitas no município de Fortaleza/CE - França, Luara da Costa (2019)
In Brazil, adolescents, mainly black males who live in the poor suburbs, are murdered or deprived of their freedom under the allegation of drug trafficking. In illegal drug possession or apprehension, law operators have the law number 11.343/2006 (targeted at criminal majority) at their disposal to base their judgement. Such law points out incriminating aspects related to nature, quantity of apprehended substances, the site and conditions in which the action took place, as well as social and personal circumstances, all of these linked to the conduct and criminal background of the person who was caught. Having as a reference the theoretical-methodological contributions of the French philosopher Michel Foucault, we searched on the criteria used by some law operators (police delegate, justice prosecutors, public defenders and judges) to classify adolescents as “consumers/users” or as “drug dealers” in the city of Fortaleza. For that, we interviewed operators and analyzed documents: legal proceedings with finished sentence; relevant legislation (Child and Adolescent Statute – ECA, Law number 11.343/2006, Jurisprudence etc.). We list enunciative scenes (seizure, hearing and sentence) as an analysis resource, in which we deal suspicious attitude, confession, penal selectivity, dark figure of crime and state racism. We have come to the conclusion that the criminalization of poor black adolescents as dangerous drug traffickers is articulated by practices and knowledge, in intersections between prohibitionism and a racist penal state, perpetuating the criminalization of a majority share of the population as from the argument of use of drugs considered illicit.